Characterization of wear debris from metal‐on‐metal hip implants during normal wear versus edge‐loading conditions. Issue 3 (8th May 2017) - Kovochich, Michael; Fung, Ernest S.; Donovan, Ellen; Unice, Kenneth M.; Paustenbach, Dennis J.; Finley, Brent L.
Abstract: Advantages of second‐generation metal‐on‐metal (MoM) hip implants include low volumetric wear rates and the release of nanosized wear particles that are chemically inert and readily cleared from local tissue. In some patients, edge loading conditions occur, which result in higher volumetric wear. The objective of this study was to characterize the size, morphology, and chemistry of wear particles released from MoM hip implants during normal (40° angle) and edge‐loading (65° angle with microseparation) conditions. The mean primary particle size by volume under normal wear was 35 nm (range: 9–152 nm) compared with 95 nm (range: 6–573 nm) under edge‐loading conditions. Hydrodynamic diameter analysis by volume showed that particles from normal wear were in the nano‐ (<100 nm) to submicron (<1000 nm) size range, whereas edge‐loading conditions generated particles that ranged from <100 nm up to 3000–6000 nm in size. Particles isolated from normal wear were primarily chromium (98.5%) and round to oval in shape. Edge‐loading conditions generated more elongated particles (4.5%) (aspect ratio ≥ 2.5) and more CoCr alloy particles (9.3%) compared with normal wear conditions (1.3% CoCr particles). By total mass, edge‐loading particles contained approximately 640‐fold more cobalt than normal wear particles. Our findings suggest that high wear conditions are a potential risk factor for adverse local tissue effects in MoM patients who experience edge loading. This study is the first to characterize both the physical and chemical characteristics of MoM wear particles collected under normal and edge‐loading conditions. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 986–996, 2018.